Characterization of thickness variations of thin dielectric layers at the nanoscale using scanning capacitance microscopy - Yanev, V.; Rommel, Mathias; Bauer, A. J.; Frey, Lothar (Journal of Vacuum Science & Technology B: Microelectronics Processing and Phenomena, 2011)
In this work, the applicability of scanning capacitance microscopy (SCM) for film thickness characterization and its sensitivity to the surface roughness on nanoscale were examined experimentally. SiO_2 layers with different film thicknesses (between 5 and 19 nm) were analyzed by conventional capacitance-voltage (C-V) measurements and using SCM in the scanning capacitance spectroscopy (SCS) mode. The influence of the film thickness on the SCM signal was studied in detail by comparison of modeled data with experimental data. The dC/dV-V characteristics measured by SCS at the nanoscale could be correlated with derivatives of conventionally measured C-V curves as well as simulated C-V characteristics for the different film thicknesses. Quantitatively comparing their peak areas, it was found that the dC/dV signal of SCS correlates with the change in the insulator thickness. The sensitivity of SCM for the detection of local variations of dielectric-layer thicknesses at the nanoscale was demonstrated by SCM mapping of crystalline high-k layers, where spatial differences of the SCM signal could be directly correlated with changes in the topography caused by film thickness variations.